2021
DOI: 10.4236/jhrss.2021.92021
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work Stress and the Work Environment in the Organization: How Job Satisfaction Affects Employee Performance?

Abstract: Research to date regarding job satisfaction such as comfort, love of work and working conditions are still a priority used in improving performance results. This is associated with too much workload. Unable to complete work due to stress factors, and less supportive work environment conditions. Managers just give up, but believe they can overcome, and finish. Several other organizations also faced the same thing. Therefore, the purpose of this study is to prove that job satisfaction can change the impact of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The result shows that the work stress score has a positive correlation with the workplace environment. The work environment is where employees engage in activities that can positively and negatively affect their ability to achieve their goals [24]. According to research, an uncomfortable atmosphere will reduce staff performance, such as productivity levels and employee morale, thereby affecting corporate objectives [25].…”
Section: Resultsmentioning
confidence: 99%
“…The result shows that the work stress score has a positive correlation with the workplace environment. The work environment is where employees engage in activities that can positively and negatively affect their ability to achieve their goals [24]. According to research, an uncomfortable atmosphere will reduce staff performance, such as productivity levels and employee morale, thereby affecting corporate objectives [25].…”
Section: Resultsmentioning
confidence: 99%
“…Breaugh et al [ 44 ] stated that a person’s desires for their work and the benefits they actually receive from it determine job satisfaction. Moreover, the contented state of mind that satisfies work requirements adds to job satisfaction [ 45 , 46 ]. People who are content and joyful in their jobs do better than those who are not [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…If a civil servant simultaneously faces various conflicts related to his/her roles or experiences interpersonal disputes at the workplace, then this individual, as he is also constantly under above mentioned stressors, will experience job burnout. 43 Ferrans 44 suggested that the inconvenience caused by shift work may affect shift workers’ physical and mental health. It will eventually reduce their quality of life.…”
Section: Introduction Literature Review and Hypotheses Developmentmentioning
confidence: 99%